STRATEGI KOMUNIKASI PEMBELAJARAN EFEKTIF (STUDI KASUS PEMBELAJARAN MATA KULIAH PAI DI FIP UNM) - Khaerun Nisa’ (Fakultas Dakwah dan Komunikasi, 2015)
Implementation of effective learning strategies in education, particularly in higher education, so that the communication strategy necessitates a learning process effective and communicative. This is done in line with the development of technology is always quite good effect in the world of education, especially in the teaching and learning process innovation efforts. Use of this technology in the communication process of teaching by faculty and student readiness in using these technologies provide multiple benefits, the students listened to the lecture material easier. In addition, the teaching process needs innovation more practical, especially the strengthening of the material as well as comprehensive search material particulars and rich enough through a network of material on the internet, has been used optimally. Meanwhile, the campus of the State University of Makassar (UNM) demanding technology-based learning, both the lecture to test and deposit of the final grade. Hence the course required to adopt the learning strategy and effective communication, is also in the process value input have made use of technological tools. So in the context of learning communication, then the presence of technology is helpful lectures comunicative and effective. This paper specifically to review the communication strategy of learning subjects of Islamic Religious Education (PAI) in the Faculty of Education, University of Makassar (UNM-FIP).